2017
DOI: 10.1097/md.0000000000006187
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of hollow viscus injury using intestinal fatty acid–binding protein in blunt trauma patients

Abstract: A delay in diagnosing hollow viscus injury (HVI) causes an increase in mortality and morbidity. HVI remains a challenge to diagnose, and there is no specific diagnostic biomarker for HVI. We evaluated the utility of intestinal fatty acid–binding protein (I-FABP) in diagnosing HVI in blunt trauma patients. Within a 5-year period, 93 consecutive patients with clinically suspected HVI at our trauma center were prospectively enrolled. The diagnostic performance of I-FABP for HVI was compared with that of other var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Only abdominal tenderness and an elevated I-FABP level were statistically significant. Several other studies showed similar results, confirming that clinical examination together with a CT scan of the abdomen plays a vital role in the early diagnosis of an HVI [23][24][25][26]. In keeping with these studies, none of the clinical features, location of injuries, or metabolic parameters we evaluated were statistically significant.…”
Section: Discussionsupporting
confidence: 82%
“…Only abdominal tenderness and an elevated I-FABP level were statistically significant. Several other studies showed similar results, confirming that clinical examination together with a CT scan of the abdomen plays a vital role in the early diagnosis of an HVI [23][24][25][26]. In keeping with these studies, none of the clinical features, location of injuries, or metabolic parameters we evaluated were statistically significant.…”
Section: Discussionsupporting
confidence: 82%
“…I-FABP is an intracellular protein specifically and abundantly expressed in intestinal epithelial cells, and its increased serum concentration represents intestinal epithelial cell damage and IB dysfunction ( Gajda & Storch, 2015 ; Wells et al, 2017 ). As a biomarker of IB dysfunction, I-FABP determination has been used in patients with necrotizing enterocolitis ( Coufal et al, 2020 ), acute mesenteric ischemia ( Salim et al, 2017 ), strangulated small bowel obstruction ( Kittaka et al, 2014 ), Crohn’s disease ( Sarikaya et al, 2015 ), blunt trauma ( Matsumoto et al, 2017 ), celiac disease ( Oldenburger et al, 2018 ), acute pancreatitis( Kupcinskas et al, 2018 ; Goswami et al, 2017 ), acute decompensated heart failure ( Kitai et al, 2017 ), chronic renal failure ( Okada et al, 2018 ), septic shock ( Sekino et al, 2017 ), psoriasis ( Sikora et al, 2019 ), and even physiological stressor-induced intestinal damage ( March et al, 2017 ). In addition to serum I-FABP, many other biomarkers are used to measure IB function ( Wells et al, 2017 ; Piton & Capellier, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although some new peptide markers have been proposed for this purpose and found promising, their reliability has yet to be scientifically proven. [18] The jejunum and ileum were found to be the most injured organs, followed by colorectal injuries, either in combination with small bowel injuries or in isolated form. This finding is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although some new peptide markers have been proposed for this purpose and found promising, their reliability has yet to be scientifically proven. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%